ADBR: Accelerated Depth-Based Routing for Underwater Sensor Networks - Andalib, Abdolreza; Abbasi Nia, Fariba; Jamshidi, Mojtaba; Shaltooki, Abdusalam Abdulla; Esnaashari, Mehdi (JITCE (Journal of Information Technology and Computer Engineering), 2022)
It is challenging to propose an efficient routing algorithm for Underwater Wireless Sensor Networks (UWSNs) in terms of packet delivery ratio, end-to-end delay of packet delivery from the source to the destination, and energy consumption. The reasons of that are UWSNs have unique characteristics (e.g. using acoustic channels instead of radio channels for communications), and they have dynamic topology due to the movement of the sensor by the water flow. Depth-Based Routing (DBR) considers one of the well-known algorithms in this context. DBR is a very simple algorithm; however, it is inefficient in terms of packet delivery rate, end-to-end delay, and energy consumption. This study we developed DBR by adding an accelerated routine to it to improve its efficiency, the proposed algorithm; called Accelerated Depth-Based Routing (ADBR). In ADBR, a simple probabilistic mechanism is used to accelerate packet forwarding and provide more multi-path to the destination. In ADBR, each node immediately delivers received packet to the destination with a probability of and follows the DBR routine with a probability of 1 – Pf. The performance of ADBR is evaluated via a set of experiments by using J-SIM simulator. Experimental results indicate the superiority of the ADBR over the DBR algorithm.